Master student's application of evidence-based knowledge and skills in Swedish healthcare practice. Issue 1 (March 2021) - Ekvall Hansson, Eva; Carlsson, Gunilla; Fänge, Agneta Malmgren
ABSTRACT: Aim: To investigate the application of evidence-based knowledge and skills in everyday healthcare practice among healthcare personnel attending a course in evidence-based practice (EBP) at the master's level. Methods: In this cross-sectional study, an evaluation of the use of instrumental, conceptual and persuasive research was performed among students attending a master's course in EBP at Lund University. Seven questions from the validated questionnaire in the Longitudinal Analysis of Nursing Education project were used. The questionnaire was distributed among 21 students at the first lecture in the course (the group before the course). Students who had participated in the course 1 (n = 15) and 2 (n = 13) years earlier received the questionnaire by ordinary mail (the group after the course). Results: The current study revealed that the majority of the students used research in their daily healthcare practice. However, the extent and type of use varied. There were differences in research use between the 'before' and 'after' groups. More specifically, the students in the group responding after the course were significantly more prone to use research in practice than the students responding before the course ( P = 0.01 and 0.04). Conclusion: An EBP course offered to master's degree students provides enhancement of evidence-based knowledge and skills, and stimulates research use in healthcare practice.